Focus Group Discussion of Internal Factors Community Sharing Trends on Self-Efficacy Photographic Images - Shahizan Ali, Mohd. Nor; Lyndon, Novel; Mohamed Salim, Neesa Ameera; Sarifin, Muhammad Ridhwan (International Journal of Psychosocial Rehabilitation, 2020)
Communications technology has played an important role in the dissemination of information to the public. This information includes the dissemination on self-efficacy photographic images which transmitted in various forms. Internet is also called as a tool to convince the public of an event. However, not all information obtained from social media is considered to be relevant and appropriate. This article dismantling the key factors which affect the younger generation (youth) which tend to do a photographic image sharing on online Public Housing Program (PHP) community. The method used is the focus groups discussion consisting of twenty- one informants aged between twenty to twenty-four years is also a youth among low income community at PHP Lembah Subang, Selangor. The study is based on internal factors (the narrative, photographic images and themes) and external (Internet and ethics). Five photographic images on self-efficacy (images that are picked from online community at PHP Lembah Subang, Selangor) displayed and should be evaluated by the informants and further sets out their views. The study found that these two factors internal and external) influence the sharing of self- efficacy photographic images to online community. In addition, the subject matter is an important factor which be assessed before the self-efficacy photographic images are shared. However, for younger generation who use low rate Internet are not fully influenced by internal factors (the narrative, photographic images and themes) in partnership photographic images online.